The Mucosal Immune System and Its Regulation by Autophagy - Kabat, Agnieszka M.; Pott, Johanna; Maloy, Kevin J. (Frontiers in Immunology, 2016)
The gastrointestinal tract presents a unique challenge to the mucosal immune system, which has to constantly monitor the vast surface for the presence of pathogens while at the same time maintaining tolerance to beneficial or innocuous antigens. In the intestinal mucosa specialized innate and adaptive immune components participate in directing appropriate immune responses towards these diverse challenges. Recent studies provide compelling evidence that the process of autophagy influences several aspects of mucosal immune responses. Initially described as a 'self-eating' survival pathway that enables nutrient recycling during starvation, autophagy has now been connected to multiple cellular responses, including several aspects of immunity. Initial links between autophagy and host immunity came from the observations that autophagy can target intracellular bacteria for degradation. However, subsequent studies indicated that autophagy plays a much broader role in immune responses, as it can impact antigen processing, thymic selection, lymphocyte homeostasis and the regulation of immunoglobulin and cytokine secretion. In this review, we provide a comprehensive overview of mucosal immune cells and discuss how autophagy influences many aspects of their physiology and function. We focus on cell-type specific roles of autophagy in the gut, with a particular emphasis on the effects of autophagy on the intestinal T cell compartment. We also provide a perspective on how manipulation of autophagy may potentially be used to treat mucosal inflammatory disorders.